Conceptual design of a passively safe thorium breeder Pebble Bed Reactor. (January 2015) - Wols, F.J.; Kloosterman, J.L.; Lathouwers, D.; van der Hagen, T.H.J.J.
Highlights: This work proposes three possible designs for a thorium Pebble Bed Reactor. A high-conversion PBR (CR > 0.96), passively safe and within practical constraints. A thorium breeder PBR (220 cm core) in practical regime, but not passively safe. A passively safe breeder, requiring higher fuel reprocessing and recycling rates. Abstract: More sustainable nuclear power generation might be achieved by combining the passive safety and high temperature applications of the Pebble Bed Reactor (PBR) design with the resource availability and favourable waste characteristics of the thorium fuel cycle. It has already been known that breeding can be achieved with the thorium fuel cycle inside a Pebble Bed Reactor if reprocessing is performed. This is also demonstrated in this work for a cylindrical core with a central driver zone, with 3 g heavy metal pebbles for enhanced fission, surrounded by a breeder zone containing 30 g thorium pebbles, for enhanced conversion. The main question of the present work is whether it is also possible to combine passive safety and breeding, within a practical operating regime, inside a thorium Pebble Bed Reactor. Therefore, the influence of several fuel design, core design and operational parameters upon the conversion ratio and passive safety is evaluated. A Depressurized Loss of Forced Cooling (DLOFC) is considered the worst safety scenario that can occur within a PBR. So, the response to a DLOFC with and without scram is evaluated for several breeder PBR designs using a coupled DALTON/THERMIX code scheme. With scram it is purely a heat transfer problem (THERMIX) demonstrating the decay heat removal capability of the design. In case control rods cannot be inserted, the temperature feedback of the core should also be able to counterbalance the reactivity insertion by the decaying xenon without fuel temperatures exceeding 1600 °C. Results show that high conversion ratios (CR  > 0.96) and passive safety can be combined in a thorium PBR within a practical operating regime, which means a thermal power of 100 MW or higher, 1000 days total residence time of the breeder pebbles and fuel pebble handling times longer than 14.5 s, like in the HTR-PM. With an increased U-233 content of the fresh driver pebbles (18 w%), breeding (CR = 1.0135) can already be achieved for a 220 cm core and 80 cm driver zone radius. While the decay heat removal is sufficient in this design, the temperature feedback of the undermoderated driver pebbles is too weak to compensate the reactivity insertion due to the xenon decay during a DLOFC without scram. With a lower U-233 content per driver pebble (10 w%) it was found possible to combine breeding (CR = 1.0036) and passive safety for a 300 cm core and 100 cm driver zone radius, but this does require more than a doubling of the pebble handling speed and a high reprocessing rate of the fuel pebbles. The maximum fuel temperature during a DLOFC without scram was simulated to be 1481 °C for this design, still quite a bit below the TRISO failure temperature. The maximum reactivity insertion due to an ingress of water vapour is also limited with a value of +1497 pcm.